The effect of temperature on the upscaling process of 6-gingerol and 6-shogaol extraction from zingiber officinale using subcritical water extraction - Mohd Sharizan Md Sarip; Nik Muhammad Azhar Nik Daud; Zuhaili Idham; Mohd Asraf Mohd Zainudin; Amirul Ridzuan Abu Bakar; Muhammad Syafiq Hazwan Ruslan; Ahmad Hazim Abdul Aziz (MDPI, 2025)
<please refer to the enclosed abstract>